2006
DOI: 10.1073/pnas.0609473103
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional signaling between calcium channels of skeletal muscle requires multiple direct and indirect interactions

Abstract: We have defined regions of the skeletal muscle ryanodine receptor (RyR1) essential for bidirectional signaling with dihydropyridine receptors (DHPRs) and for the organization of DHPR into tetrad arrays by expressing RyR1-RyR3 chimerae in dyspedic myotubes. RyR1-RyR3 constructs bearing RyR1 residues 1-1681 restored wildtype DHPR tetrad arrays and, in part, skeletal-type excitationcontraction (EC) coupling (orthograde signaling) but failed to enhance DHPR Ca 2؉ currents (retrograde signaling) to WT RyR1 levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 37 publications
5
58
0
Order By: Relevance
“…Multiple regions of RyR1 are likely to be involved in the interactions with Ca v 1.1 (Nakai et al 1998;Proenza et al 2002;Protasi et al 2002;Perez et al 2003;Sheridan et al 2006). The sites of interaction appear to be distributed over a large part of the cytoplasmic region, among them the divergent region 2 (Sheridan et al 2006), which has been mapped to the clamp domains (Liu et al 2004). Freeze-fracture studies suggest subdomains 4 and 6 as the most likely locations for contact with Ca V 1.1 (Paolini et al 2004).…”
Section: Crystal Structure Of the Amino-terminal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple regions of RyR1 are likely to be involved in the interactions with Ca v 1.1 (Nakai et al 1998;Proenza et al 2002;Protasi et al 2002;Perez et al 2003;Sheridan et al 2006). The sites of interaction appear to be distributed over a large part of the cytoplasmic region, among them the divergent region 2 (Sheridan et al 2006), which has been mapped to the clamp domains (Liu et al 2004). Freeze-fracture studies suggest subdomains 4 and 6 as the most likely locations for contact with Ca V 1.1 (Paolini et al 2004).…”
Section: Crystal Structure Of the Amino-terminal Domainmentioning
confidence: 99%
“…The b 1a carboxyl terminus is also important for E-C coupling (Beurg et al 1999;Sheridan et al 2003). Multiple regions of RyR1 are likely to be involved in the interactions with Ca v 1.1 (Nakai et al 1998;Proenza et al 2002;Protasi et al 2002;Perez et al 2003;Sheridan et al 2006). The sites of interaction appear to be distributed over a large part of the cytoplasmic region, among them the divergent region 2 (Sheridan et al 2006), which has been mapped to the clamp domains (Liu et al 2004).…”
Section: Crystal Structure Of the Amino-terminal Domainmentioning
confidence: 99%
“…RyR3/RyR1 chimeras were designed to identify regions of WT RyR1 directly associated with the DHPR during EC-coupling [20] and [21]. In this report, [ …”
mentioning
confidence: 99%
“…In the case of RyR1, this approach has shown that skeletal-type EC coupling depends on multiple regions far separated in the primary sequence (9,10). However, these studies have been hampered by the relative lack of information about the tertiary structure of RyR1.…”
mentioning
confidence: 99%